Organizational and legal support of innovation development in the agrarian sector of the economy of Ukraine - Вікторія Валеріївна Панченко (Проблеми Законності, 2017)
In the course of a long process of reform, Ukraine is trying to create a competitive, export-oriented agriculture in accordance with international standards of safety and product quality. In Ukraine is no efficient system for the transfer of innovations, the spread of modern technologies for the production and processing of agricultural products, methods and ways to organizing production and economic activity of agricultural enterprises. System analysis of the current legislation on innovation development in the agrarian sector of the Ukrainian economy proved that it is premature to assert a coherent and mutually agreed system of legal acts in this area. The legislation under consideration requires further improvement in order to enhance the appropriate level of organizational and legal support for innovation development by concentrating the state resources on the priority directions of scientific and technical updating of agricultural production, increasing the competitiveness of domestic products in the external and internal markets. To address the issues of proper organizational and legal provision of innovation development in the agrarian sector of the Ukrainian economy in order to increase the competitiveness of agriculture and promote the development of rural areas on a sustainable basis in accordance with EU standards and international standards it is necessary: to define a long-term concept of development of agriculture and rural areas, have a basis for a stable, predictable and transparent legal system aimed at improving the business climate, countering corruption and stimulating investment for the modernization of the agrarian sector, to carry out the institutional reform necessary for effective control. This will balance the approach to strengthening the competitiveness of the agrarian sector and increase exports, will promote the development of rural areas and the conservation of natural resources and the environment.